A clinicopathological study of liver disease in haemophiliacs. Issue 8 (August 1978) - Mannucci, P M; Ronchi, G; Rota, L; Colombo, M
Abstract : Chronic liver disease is not often reported in patients with haemophilia. Although a high incidence of abnormal liver function tests has been reported, the clinical significance of these findings and their relation to chronic liver disease cannot be established without a liver biopsy. The results of this procedure, carried out in 11 patients with severe haemophilia A and B, in whom SGOT had been persistently raised for three years, are reported. Five patients had chronic active hepatitis, four had chronic persistent hepatitis, one had cirrhosis, and one alcoholic hepatitis. No haemorrhagic complication followed the biopsy procedure, which was carried out in patients given prophylactic clotting factor concentrates. These results suggest that duration of abnormal liver function tests is likely to represent liver disease in haemophiliacs, and that biopsy should be considered to establish the diagnosis and plan a suitable therapeutic programme.